The Experience of Intimacy and Sexuality in Persons with Mental Illness: A Metasynthesis - Reshma Antony; Manjula Munivenkatappa; Geetha Desai (Journal of Psychosexual Health)
Mental illness has an impact on the experience of intimacy and sexuality by causing impairments in various domains of personal and interpersonal function. An in-depth exploration of the subject reveals various psychological and sociocultural factors impacting sexual functioning in persons with mental illness. This review attempts to synthesise available qualitative studies to generate interpretive themes that describe the narrative experiences of intimacy and sexuality in this population. Major and Savin-Baden’s metasynthesis method for qualitative research was used, with the modified PCO (Person, Context, Outcome) framework guiding the search strategy. A total of nine studies were obtained from a search of the electronic databases PubMed, ProQuest and Web of Science. ATLAS.ti software was used to code the primary and secondary data to generate 83 descriptive themes and 17 composite themes, which were further synthesised to create seven interpretive themes. These were About self (body, self-esteem and sexual self), mental illness (symptoms, side effects and recovery), intimate partners (negative cognitions about intimate relationships and shift in the relationship), family (dependence on family and discouraging relationships); environment (lack of privacy, lack of infrastructure and mental health professionals); others (exploitative others and untrusting others) and social integration (stigma and trust). The review establishes how the effects of mental illness pervade the experience of intimacy and sexuality by impacting their sense of self, body image, and the ability to initiate and nurture intimacy and conduct themselves in society as respectable and independent individuals. It highlights how treatment protocols and settings must incorporate the patients’ intimacy needs for holistic recovery and social integration.